Analysis of bacterial diversity and efficiency of continuous removal of Victoria Blue R from wastewater by using packed-bed bioreactor. (February 2016) - Chen, Chih-Yu; Wang, Guey-Horng; Tseng, I-Hung; Chung, Ying-Chien
Abstract: The characteristics of a packed-bed bioreactor (PBB) for continuously removing Victoria Blue R (VBR) from an aqueous solution were determined. The effects of various factors including liquid retention time (RT), VBR concentration, shock loading, and coexisting compounds on the VBR removal and bacterial community in a continuous system were investigated. The intermediates of degraded VBR and the acute toxicity of the effluent from PBB were analyzed. When the VBR concentration was lower than 400 mg/l for a two-day retention time (RT), 100% removal was achieved. During continuous operation, the efficiency initially varied with the VBR concentration and RT, but gradually increased in one to two days. Furthermore, the acute toxicity of the effluent reduced by a factor of 21.25–49.61, indicating that the PBB can be successfully operated under turbulent environmental conditions. VBR degradation involved stepwise demethylation and yielded partially dealkylated VBR species. Phylogenetic analysis showed that the dominant phylum in the PBB was Proteobacteria and that Aeromonas hydrophila dominated during the entire operating period. The characteristics of the identified species showed that the PBB is suitable for processes such as demethylation, aromatic ring opening, carbon oxidation, nitrification, and denitrification. Graphical abstract: Highlights: A novel packed-bed bioreactor (PBB) successfully removes VBR from wastewater. The effect of shock loading on VBR removal in the PBB is temporary. VBR degradation in the PBB involves stepwise demethylation. Phylogenetic analysis revealed Proteobacteria to be the dominant phylum in the PBB.